Endoplasmic reticulum stress, an important factor in the development of Parkinson's disease. (15th May 2020) - Mou, Zheng; Yuan, Yu-he; Zhang, Zhao; Song, Lian-kun; Chen, Nai-Hong
Highlights: PD-associated genetic environmental insults disturb ER balance and initiate ER stress. Disturbances of ER Ca 2+ homeostasis impacts ER stress process. ER stress initiates the activation of autophagy and inflammasomes. Many compounds are observed to protect against ER-stress-associated insults. Abstract: Similar to other types of neuronal degeneration, Parkinson's disease (PD) is characterized by the aggregation of a pathological protein, α-synuclein. The endoplasmic reticulum (ER) is the principal site of protein synthesis, quality control and degradation. Genetic mutants, environmental insults and other factors disturb ER balance and induce the accumulation of misfolded/unfolded proteins, which initiate ER stress and disturb normal cell function. ER stress perturbs Ca 2+ homeostasis and initiates the activation of autophagy and inflammasomes, which have been identified as risk factors for the development of PD. However, the mechanisms by which ER stress contributes to the processed of PD pathogenesis and development remain unclear. This review summarizes current knowledge of ER stress and highlights the principal role of ER stress in PD pathogenesis which may help reveal novel sight to illustrate the pathomechanism of PD.